Personality in Motion: How Values, Energy, and Conscious Choice Shape Identity - Alzeer, Jawad (Jurnal Pijar Mipa, 2025)
Human behavior and personality are shaped by a mix of biology, psychology, and social influences. Emotions like love and hate stem from brain chemicals like oxytocin, linking biology to emotional well-being. This study explores emotions through instincts, entropy, and quantum mechanics, combining insights from biology, psychology, and physics to understand emotional stability. The findings show that emotions are deeply personal, influenced by body chemistry, life experiences, and environment. To maintain emotional balance and personal growth, it’s important to align values, beliefs, and actions. Achieving emotional well-being requires effort, through healthy habits like good nutrition, exercise, mindfulness, and value alignment. Concepts from quantum mechanics and thermodynamics help explain the complexity of emotions, highlighting the need to nurture positivity and reduce emotional chaos.